Reproductive health ignorance in disasters: A qualitative study - Elham Rajabi; Fahimeh Ramezani Tehrani; Mehrdad Farrokhi; Mehdi Norouzi; Hamid Reza Khankeh (Journal of Education and Health Promotion)
BACKGROUND: Reproductive health (RH) is a critical human right that requires safeguarding in all contexts, including during disaster situations. Nevertheless, RH services frequently face neglect in disasters. In view of the issue’s importance and the notable gap in scientific documentation, this research was conducted to examine the underlying factors that lead to the neglect of RH in post-disaster settings in Iran. MATERIALS AND METHODS: A qualitative study was conducted using the method of content analysis, by performing in-depth semi-structured interviews in 2021–2022. Interviews were continued until the point of data saturation. The selection of participants involved a purposive sampling approach, drawing from various stakeholders, including recipients and providers of RH services, key health system and risk management officials, faculty members, relief personnel, and non-governmental organization members. The study’s setting encompassed the health system, disaster risk management organization, and the Kermanshah earthquake-affected areas. To ensure the reliability and robustness of the data, Lincoln and Goba criteria were used, and Granheim and Lundman methods were further utilized for their analysis. RESULTS: Data saturation was achieved after conducting 23 interviews. The findings of this study identified several key factors contributing to the neglect of RH in post-disaster scenarios: 1) RH: A neglected priority, irrespective of critical conditions; 2) the decline of RH in the shadow of multiple needs; and 3) lack of attention to the differences in women’s needs. CONCLUSION: The health system should prioritize RH in both normal and disaster situations. This requires promoting awareness among the general population and experts. It is recommended to develop comprehensive education programs, covering topics related to RH. Advocacy for RSH rights is recommended. Post-disaster needs and access to RH services should be prioritized in planning and resource allocation. Education on gender differences and vulnerabilities is important for officials and responders involved in risk management and post-disaster efforts.